Analisis Variasi Fonologis Bahasa Jawa - Rivaldi Saputra; Agnan Masykuri (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2023)
This research explores the phonological variations of Javanese language in three regions of Indonesia, namely Batang, Brebes, and Serang. With a focus on occupation, education, and age as social variables, the study employs phonological and lexical analysis methods to identify changes in vowel and consonant sounds, as well as lexicon within these dialects. The results reveal distinctive phonological and lexical characteristics in each region, highlighting significant differences between Batang Javanese (BJB) and Standard Javanese (BJS) as well as Javanese Banyumasan (BJBY). In conclusion, this research provides a comprehensive understanding of Javanese language variations at the dialectal level, with implications for further studies involving syntactic and semantic aspects. Recommendations for future research include expanding informant samples and delving deeper into the interplay between social factors and phonological variations.